Are plasma or CSF amyloid beta levels helpful in predicting which patients with mild cognitive impairment will progress to Alzheimer's disease (AD) or other forms of dementia?. Issue 11 (November 2016) - Gerrish, Winslow; Whitney, Allene
Abstract : EVIDENCE‐BASED ANSWER : Abnormal cerebral spinal fluid (CSF) and plasma amyloid beta (Aβ) levels are associated with cases of mild cognitive impairment (MCI) that later progress to dementia (SOR: B, meta‐analysis of cohort studies). This association does not yet have clinical utility, as likelihood ratios are close to unity, and biomarker threshold levels predicting dementia are highly variable (SOR: B, metaanalysis of cohort studies and consensus guideline).